Efek Diuretik dan Daya Melarutkan Batu Ginjal Dari Ekstrak Herba Pecut Kuda (Stachytarpheta jamaicensis (L)Vahl) - Helmi Arifin; Masitah Masitah; Elisma Elisma (Jurnal Farmasi Higea, 2010)
The herbal extract of pecut kuda’s potencies on dissolving kidney stones and it’s diuretic effect has been studied. Test dissolve kidney stones performed in vitro by dissolving the crystals or stones are usually found in the kidney. Test were carried out at 4 treatment groups, control (no extract), 0.1%; 1% and and 2% groups. In the control group, the levels of dissolved kidney stones at 52.116 ppm, while the group of 0.5%, 1% and 2% at 56.140 ppm, 61.592 ppm and 76.602 ppm respectively. One-way ANOVA test result and test advanced non-parametric Kruskal-wallis test showed that of the three consentrations of the extract has a difference in dissolving kidney stones. Diuretic effect tested on 15 white male rats were divided into 5 groups, where in the extract is administered orally. The test group was divided into a positive group (furosemide), 1 negative group (given Na-CMC) and the 3 treatment groups (125; 250 and 500 mg/kg BW). Volume of rat urine into variable observations. Based on the results of two-way ANOVA test and test advanced non-parametric Friedman test show that all three doses of the test has diuretic effect. So that the conclutions of this study are horse whip herbal extracts can dissolve kidney stones and has a diuretic effect on test animals.